A curious history of food and drink / Ian Crofton - Crofton, Ian
Ever wondered where noodles came from? How Worcester Sauce was invented? Or even who the 'Cucumber King of Burma' was? Beginning with the hippo soup eaten in Africa in 6000 BC, through to the dangerous blowfish enjoyed in contemporary Japan, A Curious History of Food and Drink reveals the bizarre origins of the food and drink consumed throughout history. From the pheasant brains and flamingo tongues scoffed by the Roman emperor Vitellius, to the unusual uses of liquorice (once a treatment for sore feet) Ian Crofton makes use of original sources including journals, cookbooks and manuals to reveal the bizarre, entertaining and informative stories behind the delicacies enjoyed by our ancestors.